Rekonstruksi Konsep Jaminan Kebendaan terhadap Aset Tak Berwujud sebagai Objek Jaminan Kredit dalam Sistem Hukum Indonesia - Sudjai Sudjai (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
The development of the digital economy has generated intangible assets such as intellectual property rights, software and digital assets with significant economic value. However, Indonesia’s property security system remains focused on tangible assets, resulting in legal uncertainty. This study employs a normative legal approach enriched with a multidisciplinary perspective. The findings indicate that intangible assets have the potential to serve as credit collateral, yet face challenges related to legal recognition, valuation standards and execution mechanisms. Therefore, a reconstruction of the legal framework is required by integrating professional valuation practices to ensure legal certainty and expand access to financing.